2011
DOI: 10.1143/jjap.50.041001
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Thin GaN from Sapphire by Laser Lift-Off Technique

Abstract: Laser lift-off of GaN from sapphire substrates has become a viable technique to increase the brightness of GaN-based light-emitting diodes (LEDs). The LEDs free from sapphire exhibit high luminous efficiency by placing highly reflective electrode on the back side. The devices serve low series resistance together with low thermal resistance taking advantages of the vertical structure. Thinner epitaxial structure is desired to serve better device performance, however, cracks in the film after the lift-off limits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
55
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 19 publications
1
55
0
1
Order By: Relevance
“…A XeCl excimer laser with a wavelength of 308 nm, which is well‐established in the display industry for low‐temperature poly‐silicon (LTPS), was irradiated through the back side of the glass substrate to reduce the adhesion between the exfoliation layer and the substrate, thus finally detaching just the upper inorganic layer from the substrate, as shown in Figure a(ii). This ILLO process is explained by localized melting, vaporizing, or dissociating of the laser‐reactive exfoliation layer as a result of the laser–materials interaction. In previous studies, we had demonstrated the easy transfer of a large‐area lead zirconate titanate (PZT) thin film and gallium nitride (GaN) thin film onto flexible substrates via a laser lift‐off (LLO) process, demonstrating that PZT, GaN, and other inorganic materials can be employed as the exfoliation layer for flexible electronics.…”
mentioning
confidence: 78%
“…A XeCl excimer laser with a wavelength of 308 nm, which is well‐established in the display industry for low‐temperature poly‐silicon (LTPS), was irradiated through the back side of the glass substrate to reduce the adhesion between the exfoliation layer and the substrate, thus finally detaching just the upper inorganic layer from the substrate, as shown in Figure a(ii). This ILLO process is explained by localized melting, vaporizing, or dissociating of the laser‐reactive exfoliation layer as a result of the laser–materials interaction. In previous studies, we had demonstrated the easy transfer of a large‐area lead zirconate titanate (PZT) thin film and gallium nitride (GaN) thin film onto flexible substrates via a laser lift‐off (LLO) process, demonstrating that PZT, GaN, and other inorganic materials can be employed as the exfoliation layer for flexible electronics.…”
mentioning
confidence: 78%
“…The laser provides a maximum output power of 8 W at 520 nm emission wavelength with a repetition rate of 200 kHz and a pulse length of <400 fs. Unlike with many other lift-off processes presented in literature, the beam profile in our setup is not widened using a beam shaper [2,3]. Instead, the beam is guided through a focusing objective and scanned across the sample by a galvanometer scanner.…”
Section: Methodsmentioning
confidence: 99%
“…Although the required energy densities are an order of magnitude higher than for conventional liftoff [2], the mostly non-thermal nature of the material decomposition at the interface may lead to a gentle lift-off. Moreover, extension of the process to UV LED structures is conceivable, as the lift-off is not directly dependent on the band gap of the semiconductor material.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Undoped, bulk GaN samples were grown by halide vapor phase epitaxy (HVPE) at Kyma Technologies, Inc. After deposition, the GaN templates were removed from their sapphire substrates using a laser lift-off process 19 and were subsequently polished down to a thickness of $400-450 lm. The surfaces were then finished with either a mechanical polish (MP) or chemical mechanical polish (CMP).…”
Section: Methodsmentioning
confidence: 99%